(3Gdbhd GdJeGe aj BOGH ONhd GdMeGes - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH SejJg HGdbhd GdJeGe ai BOGH ONhd GdMeGe CPcQ ajg BOGHkG JJYdb HGdOGNd TQYjI hCMcGe JJYdb HGdHOf WHjI s
(3BNQgG (B:s
(3bGd ai GdEQTGO hjfHZi EPG NQL Ref GdUja Cf jfGe dCfg jbGd Cf fheg HYO ONhd GdMeGe CfaY ef TQH GdOhGA hGddg JYGdi CYde gPG BNQ eG jSQ Gddg GdcQje ef Gdbhd GdJeGe ai BOGH ONhd GdMeGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jdjgG CSFdI SFd YfgG TeS GdOjf CHh YHO Gddg eMeO GdTgjQ HCHi MGeO GdUaOi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B26s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1363s
Keywords: (3GdJUha hGdBOGH GdTQYjIs